Which Pathways Should Indonesia Follow to Achieve Its Energy Development Goals into the Future? - Hanan Nugroho (The Journal of Indonesia Sustainable Development Planning, 2021)
Indonesia has developed a plan for its energy sector far into the future, however, the plan might be challenged by several international agreements that the country ratifies. The UN Report suggests several pathways for Indonesia to achieve the SDGs’ goal number 7 (affordable and clean energy). It challenges the current plan for expanding city gas networks, instead, it offers extensive uses of the electric cooking stove. It recommends that Indonesia accelerates its energy conservation efforts and reduce its energy sector’s greenhouse gasses emission by a figure which is higher than the original target. Besides, Indonesia should develop no more new coal-fired power plants and should continue to remove fossil fuel subsidies and encourage the issuance of green financing. This paper supports but also challenges the report by several arguments based on the country’s energy-economy-environment problems.